2011
DOI: 10.1016/j.psychres.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal genital and reproductive infections with verbal memory and motor deficits in adult schizophrenia

Abstract: Maternal exposure to genital and reproductive infections has been associated with schizophrenia in previous studies. Impairments in several neuropsychological functions, including verbal memory, working memory, executive function, and fine-motor coordination occur prominently in patients with schizophrenia. The etiologies of these deficits, however, remain largely unknown. We aimed to assess whether prospectively documented maternal exposure to genital/reproductive infections was related to these neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
(50 reference statements)
1
34
0
Order By: Relevance
“…Our group demonstrated that prenatal infection was related to deficits in executive function and larger size of the cavum septum pellucidum, a neuromorphologic marker of a disruption in formation of this brain structure among patients with schizophrenia (Brown et al,2009a,2009b). Furthermore, maternal genital–reproductive infections were associated with verbal memory, neuromotor, and working memory deficits in schizophrenia cases (Brown et al,2011). These studies provide further support for a neurodevelopmental impact of prenatal infection on schizophrenia and suggest that these exposures may account for at least some of the cognitive and neuroanatomic abnormalities observed in schizophrenia.…”
Section: Evidence For Prenatal Infection and Immune Abnormalities In mentioning
confidence: 99%
“…Our group demonstrated that prenatal infection was related to deficits in executive function and larger size of the cavum septum pellucidum, a neuromorphologic marker of a disruption in formation of this brain structure among patients with schizophrenia (Brown et al,2009a,2009b). Furthermore, maternal genital–reproductive infections were associated with verbal memory, neuromotor, and working memory deficits in schizophrenia cases (Brown et al,2011). These studies provide further support for a neurodevelopmental impact of prenatal infection on schizophrenia and suggest that these exposures may account for at least some of the cognitive and neuroanatomic abnormalities observed in schizophrenia.…”
Section: Evidence For Prenatal Infection and Immune Abnormalities In mentioning
confidence: 99%
“…In motor symptoms in schizophrenia, obstetric complications correlate with spontaneous movement disorders but not with drug-induced motor symptoms [51,222]. In addition, maternal genital infection was associated with impaired fine motor abilities in adult schizophrenia patients [223]. …”
Section: Neurobiology Of the Motor System In Schizophreniamentioning
confidence: 99%
“…In the Developmental Insult and Brain Anomalies and Schizophrenia Study (DIBS), based on the schizophrenia and control offspring of the CHDS birth cohort, Brown and collaborators showed that prenatal exposure to influenza or Toxoplasma gondii was associated with impairment in executive function in adult patients with schizophrenia [24]. In a second study from the DIBS, exposure to maternal genital-reproductive infections was related to verbal and neuromotor deficits in adult schizophrenia patients [25]. Moreover, maternal infection was associated in that cohort with increased size of the cavum septum pellucidum, a replicated neuromorphologic finding in schizophrenia that has embryologic origins [26].…”
Section: Epidemiological Studiesmentioning
confidence: 99%